Air gap thickness and contact area in undershirts with various moisture contents: influence of garment fit, fabric structure and fiber composition. Issue 20 (December 2015) - Frackiewicz-Kaczmarek, Joanna; Psikuta, Agnes; Bueno, Marie-Ange; Rossi, René M
The heat and water vapor transport in clothing results from fabric properties, air layers enclosed in the garment and environmental conditions. Accumulation of moisture in clothing layers intensifies this transport because of the change in thermal properties of wet fabrics and the size of air gap thickness and the contact area. This paper presents distribution of air gaps and contact areas in relation to various moisture contents in typical undershirts confectioned from fabrics with contrasting affinity to moisture. The effect of the undershirt fit, body region, fabric structure and fiber type is also discussed. The air gap thickness and the contact area were determined using three-dimensional scanning and the post-processing technique. The results show that the influence of the moisture content on the sought parameters noticeably varied among body regions and was related to the regional fit of the clothing. This variation was larger in cotton than polyester undershirts or those containing spandex, but the direct relevance of the fabric structure was not clear. Although influence of the moisture content was found, the magnitude of the air gap thickness and the contact area resulted mainly from the garment fit.